Estudo morfológico e morfométrico das fibras musculares e junções neuromusculares do músculo extensor longo dos dedos de ratos cujas mães foram submetidas à restrição proteica - Jeronimo, Léslie Cazetta (2013)
Protein energy malnutrition causes changes in several organs and systems and the earlier malnutrition occurs, more intense and permanent will be its effects. This study aimed to evaluate the morphological and morphometric aspects of the muscle fibers and neuromuscular junctions (end-plates) of the extensor digitorum longus (EDL) of rats subjected to maternal protein restriction during the periods of gestation and lactation. Wistar rats were divided into four groups: 1) control group 21 days - the offspring of mothers fed during gestation and lactation a normal protein diet (17 %); 2) restricted group 21 days - the offspring of mothers fed during gestation and lactation with a low protein diet (6 %); 3) control group 365 days - the offspring of mothers fed during gestation and lactation on a normal protein diet (17 %) until the day of weaning, and after this period the diet was standard diet until age 365 days; and 4) restricted group 365 days - the offspring of mothers fed during gestation and lactation with a low protein diet (6 %) until the day of weaning, and after this period the diet was standard diet until age 365 days. After the periods of 21 and 365 days, the male rats of each group were weighed and euthanized for the removal of the EDL muscle. The hematoxylin-eosin (HE) technique was performed for the histological analysis of the muscle fibers and histoenzymological analysis was performed using nicotinamide adenine dinucleotide tetrazolium reductase (NADH - TR). The ultrastructural study of the EDL muscle fibers was conducted using a transmission electron microscope. For the end-plates staining, muscle samples were subjected to nonspecific esterase reaction. Restricted animals with 21 or 365 days old showed a significant decrease in body weight. Histological analysis of the fibers in the restricted animals aged 21 days showed an increased amount of fetal fibers, myotubes and centered nuclei, compared with the respective control group. Histoenzymological analysis revealed a significant decrease in the area of type IIa fibers in the animals of the restricted group aged 365 days compared with the control group of the same age. Regarding the ultrastructural study, the EDL muscle of restricted animals with 21 days old showed dissolution of the Z line, the presence of lipid droplets in the midst of myofibrils, myelin figures in the subsarcolemmal and intramiofibrilar regions and nuclei in the central position in the muscle fiber line were frequent. Disorganization of the Z line and the myofibrils was also found in animals from the restricted group aged 365 days. The analysis of the end-plates showed a significant decrease in the area, and in the major and minor diameters of the restricted animals aged 21 days compared to their respective controls. These results suggest that maternal protein restriction during gestation and lactation alters the development and morphology of the offspring skeletal muscle